2
$\begingroup$

I am not sure how to show this. This is what I tried.

Proposition: If x is rational number and y is an irrational number then x+y is an irrational number.

Logically speaking this is

P=x is rational

Q= Y is irrational

R= x+y is irrational

$P\wedge Q \rightarrow R$

Explanation: What I did

$x=\frac{p}{q}$ P and Q integer

Y cannot be written as the a rational by definition

So therefore

$x+y=\frac{p}{q}+y$

Will not be a rational number as there cannot be a common denominator.

$\endgroup$
  • 1
    $\begingroup$ This doesn't do the trick as you claim what is to be shown. Assume that $x+y$ is rational show and that this implies that $y$ is rational. $\endgroup$ – Stefan Mesken Jun 17 '14 at 16:59
  • $\begingroup$ you mean I have to do the contra postive (If x+y is rational then either x is irrational or y is rational) ? $\endgroup$ – Fernando Martinez Jun 17 '14 at 17:04
  • $\begingroup$ No, note that $\sqrt 2 - \sqrt 2 = 0$ is rational, but neither is $\sqrt 2$, nor $-\sqrt 2$.Instead show: "If $x+y$ is rational and $x$ is rational, then $y$ is rational." $\endgroup$ – Stefan Mesken Jun 17 '14 at 17:10
5
$\begingroup$

$\color{green}{x=\frac{a}{b}}$ (since $x$ is rational), for $a, b \in \mathbb{Z}$.

Assume, for a contradiction, that $x+y$ is rational.

Then $x+y=\frac{p}{q}$, for $p, q \in \mathbb{Z}$.

Re-arranging: $$\color{red}y=\frac{p}{q}-\color{green}x=\frac{p}{q}-\color{green}{\frac{a}{b}}=\color{red}{\frac{pb-aq}{qb}}\left(=\frac{p'}{q'}\right),$$ which is rational (it's the quotient of two integers)-- a contradiction (since $y$ was assumed to be irrational).

$\square$

...

PS: the following is not really necessary, but it's a useful question:

Why are $pb-aq$ and $qb$ integers? I'll leave you to answer that.

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

Hint : Assume that x+y is a rational. What can you say about y=(x+y)-x ?

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Well If x is rational plus y is irrational minus x being rational y would become irrational? $\endgroup$ – Fernando Martinez Jun 17 '14 at 17:01
  • $\begingroup$ It's a proof by contradiction. Assume that the conclusion of the proposition is false : x+y is rational. Now show that would imply a contradiction with the hypothesis : "y is irrational". Indeed, y=(x+y)-x is the difference between two rational numbers, so it is a rational number. $\endgroup$ – Patissot Jun 17 '14 at 17:12
3
$\begingroup$

A slight generalization reveals the group-theoretical essence of the matter:

Lemma $ $ Let $\,Q\,$ be a nonempty subset of the additive group $\,\Bbb R\,$ (or any abelian group), and let $\,\overline Q\,$ be the complement of $\,Q\,\,$in $\,\Bbb R.\,$ Then $\,Q + \overline Q\,\subseteq\, \overline Q\iff Q - Q \subseteq Q\iff Q\,$ is a subgroup of $\,\Bbb R.\,$

Thus $\,\Bbb Q + \overline{\Bbb Q}\,\subseteq\, \overline{ \Bbb Q},\,$ i.e. rational + irrational = irrational, is simply a special case of the above, since $\,\Bbb Q\,$ is an additive subgroup of $\,\Bbb R,\,$ being closed under subtraction (so the Subgoup Test applies).

Therefore the above composition law is simply a complementary view of the Subgroup Test. See this answer for the simple proof and further examples, e.g. integer + noninteger = noninteger, and algebraic $*$ transcendental = transcendental if $\ne 0,\,$ etc.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Doubt: Must the group be abelian for the lemma to hold? $\endgroup$ – Anant Jun 18 '14 at 4:37
  • $\begingroup$ @Anant Look at the linked proof: does it require commutativity? $\endgroup$ – Gone Jun 18 '14 at 12:51
  • 1
    $\begingroup$ $g_1 - g_2 = \bar{g} \iff g_1 - g_2 + g_2 = \bar{g} + g_2 \iff g_1 = \bar{g} + g_2 \overset{\text{commutativity}}{=} g_2 + \bar{g}$. So, without commutativity, the theorem holds only for $\bar{G} + G = \bar{G}$ and not $G + \bar{G} = \bar{G}$? $\endgroup$ – Anant Jun 18 '14 at 13:40
  • $\begingroup$ @Anant But notice that the Subgroup Test can be applied in two ways, yielding both forms $$\begin{eqnarray} G - G = G &\iff& \bar G + G = \bar G\\ -G + G = G &\iff& G + \bar G = \bar G \end{eqnarray}\qquad $$ $\endgroup$ – Gone Jun 18 '14 at 14:29
  • $\begingroup$ Hmm. I am not able to think of a reason :( $\endgroup$ – Anant Jun 18 '14 at 16:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.